2017
DOI: 10.1088/1367-2630/aa8082
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the energy barrier and switching field of sub-micron magnetic islands with perpendicular anisotropy

Abstract: Using the highly sensitive anomalous Hall effect we have been able to measure the reversal of a single magnetic island, of diameter 220 nm, in an array consisting of more than 80 of those islands. By repeatedly traversing the hysteresis loop, we measured the thermally induced fluctuation of the switching field of the islands at the lower and higher ends of the switching field distribution. Based on a novel easy-to-use model, we determined the switching field in the absence of thermal activation, and the energy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
5
15
0
Order By: Relevance
“…These results show that a value of 10 9 Hz as was assumed in refs. [31,32] gives reasonable approximation.…”
Section: Rate Constantmentioning
confidence: 90%
See 2 more Smart Citations
“…These results show that a value of 10 9 Hz as was assumed in refs. [31,32] gives reasonable approximation.…”
Section: Rate Constantmentioning
confidence: 90%
“…For a permalloy island in a spin ice structure [17], K 1 > 0 and K 2 > 0 describe easy axis shape anisotropy and easy plane shape anisotropy, respectively. For CoPt islands [31,32], there is an intrinsic out of plane anisotropy and K 2 < 0 whereas K 1 ≈ 0 due to the round shape of the islands. The same system can be described by K 1 < 0 and K 2 ≈ 0 when the y-axis is chosen to be perpendicular to the island plane.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A large difference was found in the maximum field needed to switch the magnetization of different islands, likely due to variations in the thickness and composition of the metallic layers from one island to another. "Weak" islands had, for example, a maximum in the SFD at a field of 84 kA/m while "strong" islands a maximum at 184 kA/m in measurements carried out at 10 K [15]. As the temperature was increased to 300 K, the peaks shifted to the lower field by ca.…”
Section: Introductionmentioning
confidence: 98%
“…In recent experiments, de Vries et al were able to measure the SFDs of individual magnetic islands and found a large variation in the properties of the islands even though the shape and size were the same [15]. In these experiments, the SFD is only a reflection of the stochastic nature of the thermal activation since the measurements are carried out for one island at a time but with repeated sweeps of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%